2016
DOI: 10.3390/ijms17050746
|View full text |Cite
|
Sign up to set email alerts
|

“Fifty Shades” of Black and Red or How Carboxyl Groups Fine Tune Eumelanin and Pheomelanin Properties

Abstract: Recent advances in the chemistry of melanins have begun to disclose a number of important structure-property-function relationships of crucial relevance to the biological role of human pigments, including skin (photo) protection and UV-susceptibility. Even slight variations in the monomer composition of black eumelanins and red pheomelanins have been shown to determine significant differences in light absorption, antioxidant, paramagnetic and redox behavior, particle morphology, surface properties, metal chela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
148
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(153 citation statements)
references
References 73 publications
5
148
0
Order By: Relevance
“…This constraint dictates the sole production of DHICA melanin and not DHI melanin. However, all three different eumelanins, viz., DHI melanin, DHICA-DHI mixed melanin and DHICA melanin, are formed in mammalian systems [3,5,42,43]. For this to occur, obviously DHI has to be synthesized some how in comparable quantities to that of DHICA or even more.…”
Section: Modified Raper–mason Pathway For the Biosynthesis Of Eumementioning
confidence: 99%
See 1 more Smart Citation
“…This constraint dictates the sole production of DHICA melanin and not DHI melanin. However, all three different eumelanins, viz., DHI melanin, DHICA-DHI mixed melanin and DHICA melanin, are formed in mammalian systems [3,5,42,43]. For this to occur, obviously DHI has to be synthesized some how in comparable quantities to that of DHICA or even more.…”
Section: Modified Raper–mason Pathway For the Biosynthesis Of Eumementioning
confidence: 99%
“…Mammalian systems produce significant amounts of pheomelanin [42,43]. In contrast, the reports on the presence of pheomelanin in invertebrate animals and especially insects are very few [54].…”
Section: Pheomelaninmentioning
confidence: 99%
“…Although for many reaction mixtures no visible precipitations were observed and the aliquots of the reaction mixtures could be analyzed using SEC, we can not exclude the possibility that the pigment materials generated through the oxidation reactions may exist as aggregates of finely-dispersed small molecules as is discussed for MN pigments. [23][24][25] Fig.4, panel C, correlates the extent of the reactivity of the compound and the intensity of the color of the reaction mixture as evaluated through absorbance readings at 400nm. For all compounds, with the exception of (8), the absorbance increased with declining % of compound remaining up to the point when about 0% of the compound remained; typically when 0.075% v/v H 2 O 2 was present.…”
Section: Small Scale Experiments: Partmentioning
confidence: 99%
“…Recent studies found that a higher content of DHICA decreases visible light absorption and paramagnetic response relative to DHI‐based melanins, but enhances antioxidant properties. The presence of carboxyl groups shows a significant effect in the biological functions of eumelanins . Therefore, polydopamine and synthetic melanin may have more similarity with DHI‐based natural melanins.…”
Section: Introductionmentioning
confidence: 99%
“…There are many important reviews and key articles which introduce the research progress of polydopamine in different fields . In this paper, we focus on the modulation of synthetic melanin and polydopamine in chemical structures and aggregated nanostructures.…”
Section: Introductionmentioning
confidence: 99%